Dampak Globalisasi terhadap Perekonomian Indonesia - Tfuakani, Delaila Grasela; Tukan, Agnes Loda; Mangngi, Elkana Welhelmus Dimu; Dima, Enike Tje Yustin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Globalization has transformed the structure of national economies by enhancing cross-border trade, investment, and technological flows. In Indonesia, this phenomenon presents both opportunities and risks. The country benefits from increased foreign direct investment (FDI), export expansion, and access to advanced technologies, which have collectively supported economic growth and job creation. However, globalization also exposes Indonesia to external vulnerabilities, such as fluctuations in global commodity prices, balance of payments pressures, and financial market instability. This study aims to analyze the dual impact of globalization positive and negative on Indonesia’s economy, with a particular focus on international trade flows, foreign investment, industrial competitiveness, and economic inequality. Using a literature review method, the study synthesizes data and findings from relevant academic publications, policy reports, and credible sources. The analysis reveals that while globalization accelerates economic integration and productivity, it also widens income disparity and weakens the domestic industrial base in the absence of adaptive national policies. Indonesia's heavy reliance on imported goods and short-term capital inflows further increases economic fragility. Therefore, strategic policy responses are essential to mitigate the adverse effects and harness the benefits of globalization. These include strengthening domestic industries, enhancing human capital, and promoting inclusive economic development. The study concludes that globalization, if managed wisely, can serve as a catalyst for sustainable and equitable growth in Indonesia.